Evaluation of the performance of Taiba University in the function of community service and the requirements for its activation in the light of the knowledge economy - Al-Ghamdi, Afaf Ahmed; El-Sisi, Areej Hamza (Journal of Educational and Psychological Sciences, 2022)
The study aimed at evaluating the performance of Taibah University in the function of community service in the light of the knowledge economy, and determining the most important requirements for activating the performance of Taibah University in the function of community service in the light of the knowledge economy. To achieve this, the study adopted the descriptive survey method using a questionnaire of (30) items distributed on two axes and six Domains, and it was applied to a sample of (187) faculty members. The results of the study showed that the university’s role in the community service function of the total degree and its fields obtained a total average (3.13 out of 5), that is, with a performance degree (medium), and at the level of axes; got the first axis; The reality of the university’s role in the community service function got a total average of (3.12) at a medium degree, and the field of training and continuing education got an average of (3.34), then consultancy and culture dissemination with an average of (3.07), and thirdly, scientific research with an average of (2.96), all of which were graded (average), while the axis got The requirements for activating the role of the university got an overall average (3.13 out of 5) with a grade of (medium), and at the level of domains, the organizational and administrative structural requirements got the highest average (3.40), then the human requirements with an average of (3.07), both of them with a grade (medium), and finally the economic and financial requirements with an average of (2.59). ) and (weak), and it was found that there are no statistically significant differences at the level (α ≥ 0.05) between the average responses of the faculty members at Taibah University in their evaluation of the university’s performance in the community service job or in the requirements to activate its performance according to the variables (sex, academic rank). Based on the results, the researcher recommended the university to work on improving its role in the community service function in the field of scientific research, by directing research and projects in the community service function to solve its problems, and expanding enabling researchers from the community to benefit from the facilities of the research centers. in the university.